2015
DOI: 10.20965/jaciii.2015.p0697
|View full text |Cite
|
Sign up to set email alerts
|

Finding All Solutions of Systems of Nonlinear Equations Using Spiral Dynamics Inspired Optimization with Clustering

Abstract: Nowadays the root finding problem for nonlinear system equations is still one of the difficult problems in computational sciences. Many attempts using deterministic and meta-heuristic methods have been done with their advantages and disadvantages, but many of them have fail to converge to all possible roots. In this paper, a novel method of locating and finding all of the real roots from the system of nonlinear equations is proposed mainly using the spiral dynamics inspired optimization by Tamura and Yasuda [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…No timing figures reported for CDFPA to compare against. x 1 2 -2x 1 +3x 2 = −1 2x 1 2 -3.9999x 1 +6.0001x 2 = − 1.9999 0 13615 ≈ 0 - Table 6: the performance of our algorithm versus CDFPA Finally we compare our algorithm with the one proposed in [20]. Table 7 shows the systems of equations and the performance of our algorithm compared to that of the algorithm in [20].…”
Section: Problem (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…No timing figures reported for CDFPA to compare against. x 1 2 -2x 1 +3x 2 = −1 2x 1 2 -3.9999x 1 +6.0001x 2 = − 1.9999 0 13615 ≈ 0 - Table 6: the performance of our algorithm versus CDFPA Finally we compare our algorithm with the one proposed in [20]. Table 7 shows the systems of equations and the performance of our algorithm compared to that of the algorithm in [20].…”
Section: Problem (2)mentioning
confidence: 99%
“…Clearly our approach produced better precision. No timing numbers are reported in [20] to compare against. 3.93E−07 Table 7: The performance of our algorithm verses [20].…”
Section: Problem (2)mentioning
confidence: 99%
“…Luo, et al [6] proposed a hybrid approach using a chaos optimization algorithm and the quasi-Newton method, while Burden and Faires [7] used a combination of the steepest descent method and the Newton method for solving the nonlinear equation system. The latest approach is given by Sidarto & Kania in [8]. Because solving nonlinear equation systems is related to the pressure distribution in gas pipeline distribution networks, Sidarto, et al [9,10] have proposed a genetic algorithm optimization method combined with the Newton method.…”
Section: Introductionmentioning
confidence: 99%
“…However, for large systems it is observed that the convergence of the optimization process before applying the Newton-type method is rather slow. Detailed information on converting the root finding problem to an optimization process can be found in [8].…”
Section: Introductionmentioning
confidence: 99%
“…The results show a better performance in finding an optimal solution for the benchmark functions in comparison with other SDA approaches. The paper [1] and this paper propose an improvement by implementing the clustering technique. There is also a new technique in this paper in dealing with more general multimodal optimization problems, where their differential form of the objective functions is not existing or difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%